Liturgy & Sacramentality: First Perspectives from Process Oriented Psychology - Leachman, James G. (Studia liturgica, 2017)
The polarized roles of leader and participant in the liturgical assembly can be mutually antagonistic, especially when each person is unaware of both roles active in themselves and in the assembly. By growing in “role awareness” participants can discover the leader role in themselves and so more fully engage their own actuosa participatio, and leaders can discover the participant role in themselves and so better inhabit and contextualise their role in the active participation of the whole assembly. Both participants and leaders can discover the rich diversity of roles at work within themselves, in the assembly and in the world. All can discover themselves as persons in communion. [108 words]